Component-based Error Detection of P4 programs - Tóth, Gabriella; Tejfel, Máté (Acta Cybernetica, 2021)
P4 is a domain-specific language to develop the packet processing of network devices. These programs can easily hide errors, therefore we give a solution to analyze them and detect predefined errors in them. This paper shows the idea, which works with the P4 code as a set of components and processes them one by one, while calculating their pre- and postconditions. This method does not only detect errors between the components and their connections, but it is capable to reveal errors, which are hidden in the middle of a component. The paper introduces the method and shows its calculation in an example.